Impairing the maintenance of germinative cells in Echinococcus multilocularis by targeting Aurora kinase - Cheng, Zhe; Liu, Fan; Tian, Huimin; Xu, Zhijian; Chai, Xiaoli; Luo, Damin; Wang, Yanhai (PLOS Neglected Tropical Diseases, 2019)
Author summary Alveolar echinococcosis (AE), caused by infection with the metacestode larvae of the tapeworm E. multilocularis, is a lethal disease in humans. A population of adult stem cells, called germinative cells, drive the cancer-like growth of the parasite within their host and are considered responsible for disease recurrence after therapy termination. Nevertheless, benzimidazoles, the current drugs of choice against AE, show limited effects on killing these cells. Here, we describe EmAURKA and EmAURKB, two Aurora kinase members that play essential roles in regulating E. multilocularis germinative cell mitosis, as promising drug targets for eliminating the population of germinative cells. We show that targeting E. multilocularis Aurora kinases by small molecular inhibitor MLN8237 causes severe mitotic defects and eventually impairs the viability of germinative cells, leading to larval growth inhibition of the parasite in vitro. Our study suggests that targeting mitosis by MLN8237 or related compounds offers possibilities for germinative cell killing and we hope this will help in exploring novel therapeutic strategies against the disease.